Faktor-Faktor Yang Mempengaruhi Profitabilitas dan Nilai Perusahaan - Frans Papilaya; Samel Watina Ririhena (Universitas Musamus,Merauke,Papua, 2014)
This study aims to analyze and test the significance of the effect of capital structure, the growth of the company to profitability and corporate value in the telecommunications industry companies listed on the Indonesia Stock Exchange. Value of the company is investor perception of the level of success that is often associated with the company's stock price. The sampling method using purposive sampling, with some predetermined criteria, the number of samples is as much as 6 telecom industry companies. Secondary data obtained from the Indonesian Capital Market Directory (ICMD) in 2008-2012. The model is used to answer the research problem and hypothesis testing research used path analysis technique (path analysis), with the application tool SPSS version 20.0. The results showed that: 1) the capital structure and significant effect on profitability negatiff, 2) the company's growth and a significant positive effect on profitability, 3) capital structure and significant positive effect on firm value, 4) the company's growth and a significant positive effect on the value 5 companies) profitability and significant positive effect on the value enterprise.And 6) indirectly influence the capital structure, the company's growth to company value through profitability and significant positive effect.